THE POSITION OF MASHALIH AL-MURSALAH AS LEGAL EVIDENCE - Asmuni, Asmuni; Syahnan, Muhammad; hasanah, uswatun (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2024)
Mashalih al-mursalah is an important methodological concept in the development of Islamic law that often causes debate among scholars. The complexity of using this method in determining contemporary Islamic law requires in-depth study to understand its position and significance as one of the legal arguments. This study aims to analyze the position of Mashalih al-mursalah within the framework of Islamic legal methodology and evaluate the relevance of Mashalih al-mursalah in responding to modern legal challenges. The study was conducted using a normative-philosophical qualitative approach through a literature review. Data collection was carried out by examining primary and secondary sources from usul fiqh literature, classical books, and contemporary references. Data analysis techniques used descriptive-analytical, inductive-deductive, and hermeneutic methods to comprehensively interpret the concept of Mashalih al-mursalah. The results of the study found that Mashalih al-mursalah has a significant position as a legal argument, with the note that Mashalih al-mursalah can be used to establish laws in contexts that do not have a direct textual basis from the Qur'an and Hadith and has a strategic role in accommodating the development of Islamic law in accordance with social changes and the current context.